Distinct cytokine profiles in plasma and tears highlight ophthalmologic inflammation in type 2 diabetes without retinopathy - Jiménez-López, Rafael; Martín-Chaves, Laura; Gutiérrez-García, Ángel Manuel; Carmona-Segovia, Ada del Mar; Mora-Ordoñez, Begoña; Sánchez-García, Ana María; Fernández-Romero, Lourdes; Murri, Mora; Sánchez-Quintero, María José; Berteli-García, Germán; Sánchez-Chaparro, Miguel Ángel; Bodí, Vicente; et al. (Frontiers in Medicine, 2025)
IntroductionType 2 diabetes mellitus is associated with chronic inflammation and systemic complications, including ophthalmologic manifestations. While blood cytokines serve as inflammatory biomarkers, their expression in tears and correlation with systemic inflammation remain unclear. This study compared cytokine profiles in plasma and tears of well-controlled type 2 diabetes patients and controls, assessing their correlation and potential as biomarkers for disease monitoring.Materials and methodsThis cross-sectional study included 81 participants [40 with type 2 diabetes without retinopathy (T2DM group) and 41 controls (control group)] from primary care centers. Plasma and tear samples were analyzed using a multiplex immunoassay for 27 cytokines. Data were analyzed using ANCOVA (adjusted for age, hypertension, and dyslipidemia), and correlation analyses.ResultsPatients in the T2DM group exhibited distinct inflammatory profiles. Plasma levels of IL-2 (P < 0.05), IL-7 (P < 0.05), IL-9 (P = 0.001), and CCL4 (P < 0.01) were significantly lower, while tear levels of IL-6 (P < 0.01), CXCL8 (P = 0.001), IL-15 (P < 0.05), CCL5 (P < 0.001), and VEGF (P < 0.01) were elevated compared to controls. No significant correlations were observed between plasma and tear cytokines, suggesting independent regulation of systemic and ophthalmologic inflammation. Tear cytokines exhibited stronger intra-fluid correlations than plasma (98.4% vs. 66.5%), with minimal plasma-tear correlations (3.6%). Age influenced most tear cytokines (24/27 analytes) but had a weaker effect on plasma cytokines.ConclusionDespite glycemic control, patients with type 2 diabetes exhibited increased tear cytokines in the absence of diagnosed retinopathy, contrasting with reduced plasma cytokines. The lack of correlations suggests localized ophthalmologic inflammation independent of systemic inflammation, highlighting a persistent risk of retinal vascular damage in type 2 diabetes.